The Dialogical Turn in Normative Political Theory and the Pedagogy of Human Rights Education - Dale T. Snauwaert (MDPI AG, 2019)
The purpose of this paper is to explore a capacity-building pedagogical approach to human rights education as a complement to the “declarationist” approach. The basic premise of this philosophical paper is the idea of human rights as justified claims and/or demands; as such, ethical and moral justification is presupposed in the very idea of rights itself. It is argued that a dialogical turn in moral and political philosophy, in particular theoretical justifications of principles of justice, such as rights, has taken place. Given that ethical and moral justification is central to the meaning of human rights, the significance of this dialogical turn for the idea of human rights and human rights education is explored from within the idea of the logical structure of disciplines of knowledge, a discipline’s fundamental ideas and forms of thought (methods of inquiry). From within this perspective, it is argued that the dialogical nature of justification central to rights should structure the pedagogy of human rights education. It is suggested that this pedagogy entails three forms of normative dialogue—ethical, moral, and critical—that can form the normative structure of a pedagogy of human rights education. It is concluded that while awareness and respect are necessary conditions to the realization of human rights, the development of the capacity of future citizens to make, to justify, and to critique human rights claims is also necessary for the realization of human rights.